PENGHAPUSAN REMISI BAGI KORUPTOR DALAM PERSPEKTIF UNDANG-UNDANG NOMOR 12 TAHUN 1995 TENTANG PEMASYARAKATAN (Jurnal Hukum Mimbar Justitia, 2015)
Corruption in Indonesia has been categorized as an extraordinary crime (extraordinary crime) for devastating, not only the country's financial and economic potential of the country, but also has destroyed the pillars of socio-cultural, moral, political and legal order or national security. With the incredible title, then appeared the discourse for the removal of remission for corruption, so it is then reap the pro and contra among the people.As for the identification of the problem in writing this article the author limit as to whether the abolition of remissions for the corruptors is in conformity with the existing laws, or actually even contrary to human rights. The method used in this study using normative juridical approach, the research done by basing on literature data or secondary data. Based on these results, that the abolition of remission to criminals is not in accordance with the rules of the applicable legislation, especially Regulation No. 12 Year 1995 on Corrections, particularly clause 14 subsection (1) points i, which states that "Prisoners are entitled to a reduction in criminal past (remission)". Therefore, if the Government intends to provide a more powerful deterrent effect against criminal act of corruption, then the Government should first rule synergize legislation governing the granting remission to prisoners, so there is no overlapping policies.Keywords: Corruption, Remission, Objective Punishment.